Peran E-WOM dan Citra Merek terhadap Niat Beli Smartphone oleh Youtube Viewers - Baiquni, Muhammad (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Smartphones in today's era are a basic necessity especially for those who have high mobility. No less advanced than technological developments, innovation in the telecommunications world is also one of the biggest contributors to the dissemination of information in society or commonly called social media. This study aims to measure the influence of Electronic Word of Mouth (e-WOM) that occurs in YouTube social media on the intention to buy Samsung Galaxy S10 smartphones through the brand image as a mediating variabel. The type of method used in this research is quantitative by using Path Analysis. This study has positive results between influences e-WOM on the purchase intention, while there was a positive influence between e-WOM on the brand image variabel and the brand image variabel had a positive effect on the purchase intention. Further research may include price and product quality.